Ded na si lolo - Paulate, Roderick; Alajar, Gina; Oropeza, Elizabeth
A large family with lots of issues gather together to mourn the death of the family patriarch. But getting in the way of their genuine grief are a bunch of superstitions about the dead, and the family's inability to deal with their issues in a civilized way.- Written by ledster.